1984
DOI: 10.4315/0362-028x-47.8.598
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Processing and Storing Oyster Meats on Concentrations of Indicator Bacteria, Vibrios and Aeromonas hydrophila

Abstract: Oyster meats were examined from three commercial processing plants at different stages of processing and storage for four standard indicator bacterial groups, five species of vibrios reported to be associated with shellfish associated gastroenteritis, and Aeromonas hydrophila. Processing reduced the overall microbial load, but the individual bacterial groups examined remained statistically the same throughout processing. Upon storage, the concentration of Vibrio parahaemolyticus significantly declined with a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Contamination of these shellfish by pathogenic Vibrio species cannot be controlled by restricting faecal contamination of growing water so the rationale of shellfish sanitation programmes has limited application. Raw seafood and shellfish should be kept at refrigeration temperature (less than 5°C) or placed on ice immediately after harvesting or processing to prevent multiplication to numbers likely to cause disease (Hood, Baker & Singleton, 1984;Fletcher, 1985;Reily & Hackney, 1985;Saxena & Kulshrestha, 1985;Ingham & Potter, 1988). It is noteworthy that although V. vulnificus is unable to survive well in whole oysters at near-freezing temperatures (Oliver, 1981), there has been at least one reported case of infection following consumption of refrigerated raw oysters (Johnston, Andes & Glasser, 1983).…”
Section: Consumption Of Contaminated Foodstuffsmentioning
confidence: 99%
“…Contamination of these shellfish by pathogenic Vibrio species cannot be controlled by restricting faecal contamination of growing water so the rationale of shellfish sanitation programmes has limited application. Raw seafood and shellfish should be kept at refrigeration temperature (less than 5°C) or placed on ice immediately after harvesting or processing to prevent multiplication to numbers likely to cause disease (Hood, Baker & Singleton, 1984;Fletcher, 1985;Reily & Hackney, 1985;Saxena & Kulshrestha, 1985;Ingham & Potter, 1988). It is noteworthy that although V. vulnificus is unable to survive well in whole oysters at near-freezing temperatures (Oliver, 1981), there has been at least one reported case of infection following consumption of refrigerated raw oysters (Johnston, Andes & Glasser, 1983).…”
Section: Consumption Of Contaminated Foodstuffsmentioning
confidence: 99%
“…Recently, Buchanan (4) alternatively suggested that the species may represent a significant "new" food-borne pathogen and hypothesized that foods may be important in the dissemination of the microorganism. The basis for this hypothesis was the pathogenicity of the species in fish and reptiles (10), its frequent isolation from various foods of animal origin (1,3,7,8,11,12,14,15,20), and the psychrotrophic nature of the species (S. A. Palumbo, D. R. Morgan, and R. L. Buchanan, J. Food Sci., in press).…”
mentioning
confidence: 99%
“…The most commonly used enrichment medium for all vibrios of medical interest is alkaline peptone water. Salt colistin broth, glucose salt teepol broth, and arabinose-ethyl violet broth have been recommended for enrichment of V. parahaemolyticus but not for other species; alkaline bile peptone water has been recommended for V. cholerae but has not been evaluated for other species (40,67,69,93,183,204). Incubation times of 6 to 18 h at 35 to 370C have commonly been used for enrichment (6 h, optimum), although a new procedure designed to recover V. cholerae involves incubation in alkaline peptone water at 420C for 18 h (40).…”
Section: Isolation From Environmental Sourcesmentioning
confidence: 99%
“…Various studies have determined the effects of storage on the concentration of vibrios in oysters and clams, both before and after shucking (67,69). Storage of clams at the usual cold temperatures appears to have little effect on the generally low levels of vibrios present.…”
Section: Survival Of Pathogenic Vibrios In Stored Shellfishmentioning
confidence: 99%